Mutational analysis of Rift Valley fever phlebovirus nucleocapsid protein indicates novel conserved, functional amino acids - Mottram, T; Li, P; Dietrich, I; Shi, X; Brennan, B; Varjak, M; Kohl, A (Public Library of Sciences, 2017)
Rift Valley fever phlebovirus (RVFV; Phenuiviridae, Phlebovirus) is an important mosquito-borne pathogen of both humans and ruminants. The RVFV genome is composed of tripartite, single stranded, negative or ambisense RNAs. The small (S) segment encodes both the nucleocapsid protein (N) and the non-structural protein (NSs). The N protein is responsible for the formation of the viral ribonucleoprotein (RNP) complexes, which are essential in the virus life cycle and for the transcription and replication of the viral genome. There is currently limited knowledge surrounding the roles of the RVFV nucleocapsid protein in viral infection other than its key functions: N protein multimerisation, encapsidation of the RNA genome and interactions with the RNA-dependent RNA polymerase, L. By bioinformatic comparison of the N sequences of fourteen phleboviruses, mutational analysis, minigenome assays and packaging assays, we have further characterised the RVFV N protein. Amino acids P11 and F149 in RVFV N play an essential role in the function of RNPs and are neither associated with N protein multimerisation nor known nucleocapsid protein functions and may have additional roles in the virus life cycle. Amino acid Y30 exhibited increased minigenome activity despite reduced RNA binding capacity. Additionally, we have determined that the N-terminal arm of N protein is not involved in N-L interactions. Elucidating the fundamental processes that involve the nucleocapsid protein will add to our understanding of this important viral protein and may influence future studies in the development of novel antiviral strategies.